Surya Buana Senior High School Strategy in Facing Competition in The Era of Globalization - Fahmi, Ahmad Khoirur Rijal (International Research-Based Education Journal, 2022)
This research aims to determine the educational strategy of SMA Surya Buana in facing competition in an era that describes globalization. Researchers used a descriptive approach method. The research results found were Surya Buana High School educational strategies, including: (a) analyzing the internal and external environment through SWOT analysis; (b) Formulation of the vision and mission of educational institutions; (c) Determine the long-term and short-term goals of the educational organization; (d) Designing policies in educational institutions for the decision-making process; (e) Strategic planning of educational organization programs; and (f) Design of each implementation process